Between a postulate and the reality: on the problem of ‘russianness’ and ‘non-russianness’ – not only – Leontyev’s ideas - Broda, Marian (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The uniqueness and importance of Konstantin Leontyev’s thought in the Russian intellectual and cultural tradition stems from the fact that it creates a viewpoint essentially transcendental as compared with what is central, dominant and mainstream. Leontyev’s way of problematizing basic principles, assumptions and socio-institutional correlates of this tradition introduces the need – and at the same time creates an opportunity – for a real problematization of the alleged ‘Russianness’ or ‘non-Russianness’ of his ideas. At a closer inspection, it turns out that the ‘Russianness’ or ‘non-Russianness’ is not so much a quality of Leontyev’s concept itself, but above all a characteristic of the ways in which its Russian interpreters understand the world. What one is faced with, in fact, is the postulated sense of not only Leontyev’s concept, but also of the ‘Russianness-non-Russianness’ relationship itself. Hence the main question to be posed is: why would one postulate them – for what purpose and with what outcome – in this particular way?